The Role of Exosome MicroRNA-103 in the Proliferation and Invasion of Hepatoma Cells and Its Mechanism: MicroRNA-103 and Invasion of Hepatoma - Lin, Yushi; Shi, Fengmei; Yan, Junyao; Sui, Zhongyuan; Sun, Bo; Xu, Guangwei (Cellular and Molecular Biology, 2022)
Liver cancer (HCC) is a common malignant tumor whose incidence is increasing worldwide, but existing chemotherapeutic agents are not ideally effective drugs and have considerable resistance to chemotherapy. Exosome microRNA-103 plays an important role in the proliferation and invasion of liver cancer cells. The purpose of this article is to investigate the role and mechanism of exosome microRNA-103 in hepatocellular carcinoma cell proliferation and invasion. 84 patients with hepatocellular carcinoma diagnosed in a hospital from June 2017 to June 2020 were selected. The average age was 60.13±6.99 years. When the patient was fasting, 3 mL of peripheral venous blood was taken. And 50 healthy control groups were established, with an average age of 59.98±8.18 years old. 3 ml of peripheral venous blood was collected on an empty stomach to compare the cell proliferation rate and invasion rate. The results of the study showed that the number of stage III hepatocellular carcinoma cells invaded at 6h was 68.9, and it changed to 89.4 at 12h, and 106.4 at 24h; compared with that, the cell invasion rate in stage IV was higher. The number of stage IV hepatocellular carcinoma invasions at 6h was 68, which changed to 94.5 at 12h and 112.4 at 24h.